Factors Affecting Participation of People in Solid Waste Management in Luang Prabang District - Souksavath, vongsengphet; CHANTHAVONE , Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purposes of this study were to assess the level of solid waste management practices among residents of Luang Prabang; to examine the level of public participation in solid waste management in Luang Prabang city; and to identify the factors influencing public participation in solid waste management. The research sample consisted of 389 residents of Luang Prabang city, Luang Prabang Province. Data were collected using a questionnaire and analyzed using frequency, percentage, mean, standard deviation, and enter multiple linear regression. The findings were The overall level of solid waste management practices among residents was good. The practices were ranked in descending order as: Reduce, Repair, Reject, Recycle, and Reuse. The level of public participation in solid waste management was high. Participation aspects were ranked from highest to lowest as: Benefits, Implementation, Evaluation, and Decision-Making. Four key factors were found to influence public participation in solid waste management: government support, expected outcomes, community leadership, and access to information. The regression analysis showed that these factors collectively accounted for 76.36% of the variance in public participation.